Biocatalytic regioselective O-acylation of sesquiterpene lactones from chicory: a pathway to novel ester derivatives - Mosheim, Juan Rodriguez; Ruggieri, Francesca; Humeau, Catherine; Hance, Philippe; Willand, Nicolas; Hilbert, Jean-Louis; Heuson, Egon; Froidevaux, Rénato (ChemBioChem, 2024)
International audience We report the first biocatalytic modification of sesquiterpene lactones (STLs) found in the chicory plants, specifically lactucin (Lc), 11β,13dihydrolactucin (DHLc), lactucopicrin (Lp), and 11β,13-dihydrolactucopicrin (DHLp). The selective O-acylation of their primary alcohol group was carried out by the lipase B from Candida antarctica (CAL-B) using various aliphatic vinyl esters as acyl donors. Perillyl alcohol, a simpler monoterpenoid, served as a model to set up the desired O-acetylation reaction by comparing the use of acetic acid and vinyl acetate as acyl donors. Similar conditions were then applied to DHLc, where five novel ester chains were selectively introduced onto the primary alcohol group, with conversions going from >99 % (acetate and propionate) to 69 % (octanoate). The synthesis of the corresponding O-acetyl esters of Lc, Lp, and DHLp was also successfully achieved with near-quantitative conversion. Molecular docking simulations were then performed to elucidate the preferred enzyme-substrate binding modes in the acylation reactions with STLs, as well as to understand their interactions with crucial amino acid residues at the active site. Our methodology enables the selective O-acylation of the primary alcohol group in four different STLs, offering possibilities for synthesizing novel derivatives with significant potential applications in pharmaceuticals or as biocontrol agents. Nous rapportons la première modification biocatalytique de lactones sesquiterpéniques (STL) présentes dans la chicorée, à savoir la lactucine (Lc), la 11β,13dihydrolactucine (DHLc), la lactucopicrine (Lp) et la 11β,13-dihydrolactopicrine (DHLp). La lipase B de Candida antarctica (CAL-B) a procédé à la O-acylation sélective de leur groupe alcool primaire en utilisant divers esters vinyliques aliphatiques comme donneurs d'acyle. L'alcool périllylique, un monoterpénoïde plus simple, a servi de modèle pour mettre en place la réaction d'O-acétylation souhaitée en comparant l'utilisation de l'acide ...